Management factors affecting service quality for members of the Association of Persons with Disabilities, Sisaket Province - Kanhabutr, Amporn; Kongyoungyune, Dr.Rungradit (Journal of Dhamma for Life, 2023)
The aims of this study encompassed three main objectives: firstly, to gauge the level of organizational management factors within the Association of Persons with Disabilities in Sisaket Province; secondly, to assess the quality of services extended to members of the Association; and thirdly, to explore the correlation between organizational management factors and service quality. Data was collected using a questionnaire, and the sample comprised individuals with disabilities who were members of the Association in Sisaket Province, totaling 272 residents. Statistical analyses included frequency, percentage, mean, standard deviation, Pearson product-moment correlation coefficient, and multiple regression analysis. The findings revealed the following: 1) The overall level of organizational management factors within the Association of Persons with Disabilities in Sisaket Province was high. Upon closer examination of each component, coordination emerged as the foremost factor, followed by organizational management, planning, command, and control, respectively. 2)The overall service quality for members of the Association in Sisaket Province was deemed high. An itemized breakdown identified reliability as the foremost factor, followed by customer response. The tangible aspects of service, specifically instilling confidence in customers and understanding their needs, also ranked high. 3) The investigation into the relationship between organizational management factors and service quality for the Association of Persons with Disabilities in Sisaket Province revealed statistically significant positive relationships for each factor at the 0.01 level.